UPAYA OPTIMALISASI MAHARAH KITABAH MELALUI MODEL PEMBELAJARAN BERBASIS PROYEK PADA MATERI AL-JUMLAH - HASTANG HASTANG (Institut Agama Islam Negeri (IAIN) Bone, 2018)
This study aims to optimize the ability of students to write Arabic sentences (maharah kitabah) through project-based learning models in al-Jumlah material. This study used descriptive qualitative method. The subjects of the study were students at the second semester of IAIN Bone, which were from class PBA1, PBA2, PBA3, PS6, PGMI4, and PGMI 5. Data was collected through tests, observations, and interviews with instrument performance, observation guidelines, and interview guidelines. The data collected from the results of this study will be analyzed using qualitative data analysis.The results of the study show: 1) The application of project-based learning models in al-quantity material is carried out in several stages, starting from determining the theme of writing, determining sources, collecting material (writing rules) and mufradat (vocabulary), compiling sentences and discussing them collaboratively with members team, up to presenting in front of other teams. 2) Students are generally able to make al-Jumlah based on the elements of the sentence that have been learned. For example, making al-Jumlah Ismiyah consisting of mubtada' and khabar, al-Jumlah al-Fi'liyah consisting of fi'il, fa'il, and maf'ul by using sentences that are in accordance with the attached image and also able to write with the correct writing and harakat. Based on the results of the study, it can be concluded that the project-based learning model can optimize the student achievement of high-level students in al-Jumlah material.